Pontinia (FedOA - Federico II University Press, 2024)
The volume provides an overview of the results obtained in the Final Synthesis Laboratory in Modern Restoration, conducted by professors Gianluigi de Martino and Marella Santangelo within the Master's Degree Course in Architectural Design at the University of Naples "Federico II". Through work on the city of Pontinia, the laboratory selected and investigated the heritage of modern architecture produced during the “Fascist Ventennio”, proposing restoration projects capable of combining historical memory with an innovative vision. The aim was to envision an alternative future for the city, capable of responding to contemporary urban transformation needs through various design experiments. The volume is divided into four sections, each dedicated to different aspects of the restoration and design process, offering in-depth readings and practical insights. Through contributions from both professors and students, the concepts of conservation and innovation in urban heritage are explored, with particular attention to the relationship between the original fabric of the founding city and its contemporary evolution. The volume concludes with a photographic review of the exhibition held at the Museum of the Pontine Marshes in June 2022, providing a comprehensive view of the laboratory's outcomes and their integration into the local community.